Eksplorasi Kebutuhan Pelanggan dari Produk Backlog untuk Pengembangan Produk Berkelanjutan - Permatasari, Indah; Santana, Ade Raka (AI Society & STMIK Indonesia, 2025)
In the digital era, sustainable software development faces challenges in meeting dynamic user needs while ensuring data management security and efficiency. Effective methods are needed to create an adaptive product backlog. This study uses Focus Group Discussion (FGD) involving five experts to identify customer needs in sustainable products. The research aims to formulate a backlog that encompasses multi-tenant security, API integration, and efficient data management. FGD results indicate that tenant security and CI/CD implementation are essential for continuous updates, while performance statistics are necessary for data-driven decision-making. This study recommends using the AHP method to establish numeric priorities and the Delphi method to achieve expert consensus. These results support the development of a backlog that is more responsive to market changes and needs.